Kerugian Keuangan Negara Yang Berimplikasi Tindak Pidana Korupsi - Andreas Lumme (Jurnal Pemberdayaan Hukum, 2011)
Basic Problems in the discussion is a perspective of the perspective of criminal law agains corruption and the state finance act which harm the state treasury. The methode is the normative approach, combined with a practical approach. The state treasury according to legal perspective of the criminal act of corruption has abroad meaning, that covers the emntire wealth of the country......